Inhibitory Effect of Celery Extract (Apium Gravolens Linn) On Blood Pressure Reduction in Hypertension Elderly in Iman Clinic - Ahmad, Amaluddin; Rahman, Shahrul (Universitas Muhammadiyah Sumatera Utara, 2022)
Abstract Hypertension is a cardiovascular disease which by definition is a condition where the systolic blood pressure is 130 mmHg or more and the diastolic blood pressure is more than 80mmHg. This disease is one of the risk factors for many diseases that exist in the world such as myocardial infarction, shock, kidney failure, and many more. Celery is a plant that can be used as medicine, its properties lower blood pressure. This study aims to analyze the effect of celery extract on lowering blood pressure in the elderly who have hypertension at the faith clinic. This study used an experimental study with pretest and posttest methods where the sample used was 36 samples which were divided into the experimental group and the control group. The sample is the elderly ( 55 years) who follow the chronic disease program at Iman Martubung Clinic. The results of this study indicate that the average decrease in blood pressure is 12.78 mmHg in systolic with an average systolic blood pressure of 141.6 mmHg pretest and posttest 128.8 mmHg, in diastolic there is an average decrease of 7.77 mmHg with the average diastolic blood pressure pretest was 82.7 mmHg and posttest was 75 mmHg in the experimental group, while in the control group there was a significant increase in blood pressure. These results are also supported by non-parametric statistical tests, with a significance value of p value value with a significance level of = 0.005. The significance value based on the Wilcoxon statistical test was 0.001 on systolic blood pressure and 0.001 on diastolic blood pressure. There is an effect of celery extract (Apium gravolens Linn) on reducing blood pressure in the elderly at Iman clinic.